Production and Income Risk Analysis Oil Palm (Elaeis guinensis Jacq) Farming - Galih Basuki Nugroho; Yossie Yumiati; Ana Nurmalia (UNIVED Press, Dehasen University Bengkulu, 2023)
The purpose of this study was to determine the production and income risks of oil palm plantations in Lubuk Bento Village. This survey was conducted in Lubuk Bento township, Pondok Suguh sub-district, Mukomuko district. The method used was simple random sampling with a sample of 44 farmers out of 290 oil palm farmers in Lubuk Bento Village. Income analysis and CV coefficient of variation studies were used for data analysis. The results showed that the production risk was 0.08 (0.08 <0.5) which means that the production risk of farmers' farms is small. The value of income obtained by farmers amounted to RP. 7,127,209/month, and revenue of RP. 11,110,080/month. The total cost is RP. 3.982. 601/month.